Hybrid energy harvesting technology: From materials, structural design, system integration to applications. (March 2021) - Liu, Huicong; Fu, Hailing; Sun, Lining; Lee, Chengkuo; Yeatman, Eric M.
Abstract: The last decade has witnessed significant advances in energy harvesting technology for the realization of self-charging electronics and self-powered wireless sensor nodes (WSNs). To conquer the energy-insufficiency issue of a single energy harvester, hybrid energy harvesting systems have been proposed in recent years. Hybrid harvesting includes not only scavenging energy from multiple sources, but also converting energy into electricity by multiple types of transduction mechanisms. A reasonable hybridization of multiple energy conversion mechanisms not only improves the space utilization efficiency but can also boost the power output significantly. Given the continuously growing trend of hybrid energy harvesting technology, herein we present a comprehensive review of recent progress and representative works, especially focusing on vibrational and thermal energy harvesters which play the dominant role in hybrid energy harvesting. The working principles and typical configurations for piezoelectric, electromagnetic, triboelectric, thermoelectric and pyroelectric transduction effects are briefly introduced. On this basis, a variety of hybrid energy harvesting systems, including mechanisms, configurations, output performance and advantages, are elaborated. Comparisons and perspectives on the effectiveness of hybrid vibrational and thermal harvesters are provided. A variety of potential application prospects of the hybrid systems are discussed, including infrastructure health monitoring, industry condition monitoring, smart transportation, human healthcare monitoring, marine monitoring systems, and aerospace engineering, towards the future Internet-of-Things (IoT) era. Highlights: A systematic and comprehensive review of hybrid energy harvesting systems. ·Piezoelectric, electromagnetic, triboelectric, thermoelectric and pyroelectric effects and their hybrid use are reviewed. Typical configurations, mechanisms and their performance are discussed and compared. Typical applications for hybrid energy harvesting mechanisms and systems are discussed and summarized. Future opportunities and directions are mapped following the discussion on existing challenges and applications.